Influence of Music on the Behaviors of Crowd in Urban Open Public Spaces - Meng, Qi; Zhao, Tingting; Kang, Jian (Frontiers in Psychology, 2018)
Sound environment plays an important role in urban open spaces, yet studies on the effects of perception of the sound environment on crowd behaviours have been limited. The aim of this study, therefore, is to explore how music, which is considered an important soundscape element, affects crowd behaviours in urban open spaces. On-site observations were performed at a 100 m x 70 m urban leisure square in Harbin, China. Typical music was used to study the effects of perception of the sound environment on crowd behaviours; then, these behaviours were classified into movement (passing by and walking around) and non-movement behaviours (sitting). The results show that the path of passing by in an urban leisure square with music was more centralised than without music. Without music, 8.3% of people passing by walked near the edge of the square, whereas with music, this percentage was zero. In terms of the speed of passing by behaviour, no significant difference was observed with the presence or absence of background music. Regarding the effect of music on walking around behaviour in the square, the mean area and perimeter when background music was played were smaller than without background music. The mean speed of those exhibiting walking around behaviour with background music in the square was 0.296 m/s slower than when no background music was played. For those exhibiting sitting behaviour, when background music was not present crowd density showed no variation based on distance from sound source. When music was present, it was observed that as the distance from the sound source increased, crowd density of those sitting behaviour decreased accordingly.